PENGARUH PEMBERIAN MOTIVASI DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA KARYAWAN KANTOR (STUDI PADA PT. ANDIKA PERMATA SAWIT LESTARI PEKANBARU) - Nely Meilani; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted at the PT. Andika Permata Sawit Lestari Pekanbaru, as for the purpose of this research is to know the influence of the giving of the motivation and discipline work against employee accomplishments (study at PT. Andika Permata Sawit Lestari Pekanbaru). Granting of motivation and discipline work as independent variables (X1, X2) while the employee's achievements as the dependent variable (Y). The problem in this research is the State of the number of employees at the PT. Andika Permata Sawit Lestari Pekanbaru who experience fluctuations every year, seen from the number of employees in the last 5 years. The sample of this research as much as 49 respondents. Data obtained from the results of a questionnaire and further processed and then tested with stats through the program SPSS. From the results of testing performed indicates that giving motivation and discipline work positive effect against employee accomplishments (study on PT. Andika Permata Sawit Lestari Pekanbaru).Keywords: Motivation, discipline, work and achievements of the Work of employees